Overexpression of Interleukin-15 Increases Susceptibility to Lipopolysaccharide-Induced Liver Injury in Mice Primed with Mycobacterium bovis Bacillus Calmette-Guérin - Yajima, Toshiki (American Society for Microbiology, 2004)
Mice primed with Mycobacterium bovis bacillus Calmette-Guérin (BCG) are highly sensitive to lipopolysaccharide (LPS)-induced liver injury and lethality. We found that interleukin-15 (IL-15) transgenic (Tg) mice primed with BCG were more susceptible to LPS-induced liver injury than non-Tg mice. The numbers of CD44(+) CD8(+) T cells expressing intracellular gamma interferon (IFN-γ) significantly increased in the livers of BCG-primed IL-15 Tg mice after LPS injection, and the depletion of CD8(+) T cells from BCG-primed IL-15 Tg mice completely abolished the susceptibility to LPS-induced lethality. Liver T cells from BCG-primed IL-15 Tg mice produced IFN-γ in vitro in response to LPS, which was inhibited by the addition of anti-IL-12 monoclonal antibody (MAb). In vivo treatment with anti-IL-12 MAb inhibited the appearance of CD44(+) CD8(+) T cells expressing intracellular IFN-γ after LPS injection. These results suggest that the overexpression of IL-15 increases susceptibility to LPS-induced liver injury in BCG-primed mice via bystander activation of CD8(+) T cells.